Differentiation of Plio-Pleistocene Hominids. II. Sexual Dimorphism - Kaszycka, Katarzyna (Anthropological Review, 1985)
On the basis of literature the author presented and discussed the problem of morphological variability in the australopithecines. Particular attention was payed to sexual differences in Hominoids and Hominids and the taxonomic consequences of explaining the variability in the australopithecines by sexual dimorphism.